Isher Judge Ahluwalia, Industrial Growth in India: Stagnation Since the Mid-Sixties, Delhi, Oxford University Press, 1985, xxiv + 235 pp. - Martínez del Campo, Manuel (Estudios de Asia y África, 1986)
-